Implementation of a Berkah Integrated Service and Referral System Policy in Handling the Poor in Pandeglang District Banten Province - Riyanto Riyanto; Fernandes Simangunsong; Eko Budi Santoso; Ika Sartika (International Journal of Economics Development Research (IJEDR), 2023)
After the Covid-19 pandemic, the economy in most countries worldwide suffered severe setbacks, including those classified as developed nations. According to World Bank data, nearly 700 million people currently endure extreme poverty, prompting diverse countries to devise policies aimed at alleviating poverty. This study aims to address three key questions: 1) How is the policy implemented? 2) What are the factors contributing to success or failure, and what efforts are made to mitigate determinants of failure in policy implementation? 3) How innovative is the policy implementation? Employing a descriptive qualitative research method, this study utilizes Prof. Muchlis Hamdis' Policy Implementation model for analysis. The findings of this research indicate that: 1) The implementation of the BERKAH Integrated Service and Referral System policy can be considered successful, as evidenced by a reduction in poverty rates, adherence to standards and procedures, efficient resource utilization (human, asset, financial, and technological), and streamlined policy execution. 2) Twelve factors were identified as influencing success, including consistency in policy content derivation and specification, alignment with central-level policies, absence of authority abuse, strong learning mechanisms, effective networking among policy implementers, and adequate resources and technological precision. However, three factors were found to contribute to failure: insufficient budget allocation, low motivation among policy implementers, and lack of policy information dissemination. 3) The study also identifies two significant innovations: cultural adaptation in theoretical approaches and regulatory innovation involving changes from regent regulations to regional regulations.